Chasing the Origin of Viruses: Capsid-Forming Genes as a Life-Saving Preadaptation within a Community of Early Replicators - Jalasvuori, Matti; Mattila, Sari; Hoikkala, Ville (PLOS ONE, 2015)
Virus capsids mediate the transfer of viral genetic information from one cell to another, thus the origin of the first viruses arguably coincides with the origin of the viral capsid. Capsid genes are evolutionarily ancient and their emergence potentially predated even the origin of first free-living cells. But does the origin of the capsid coincide with the origin of viruses, or is it possible that capsid-like functionalities emerged before the appearance of true viral entities? We set to investigate this question by using a computational simulator comprising primitive replicators and replication parasites within a compartment matrix. We observe that systems with no horizontal gene transfer between compartments collapse due to the rapidly emerging replication parasites. However, introduction of capsid-like genes that induce the movement of randomly selected genes from one compartment to another rescues life by providing the non-parasitic replicators a mean to escape their current compartments before the emergence of replication parasites. Capsid-forming genes can mediate the establishment of a stable meta-population where parasites cause only local tragedies but cannot overtake the whole community. The long-term survival of replicators is dependent on the frequency of horizontal transfer events, as systems with either too much or too little genetic exchange are doomed to succumb to replication-parasites. This study provides a possible scenario for explaining the origin of viral capsids before the emergence of genuine viruses: in the absence of other means of horizontal gene transfer between compartments, evolution of capsid-like functionalities may have been necessary for early life to prevail.